Administrative Processes Efficiency Measurement in Higher Education Institutions: A Scoping Review - Dulce Alvarez-Sández; Karla Velázquez-Victorica; Alejandro Mungaray-Moctezuma; Aída López-Guerrero (MDPI AG, 2023)
Universities, like any organization, must attend to the needs of the environment to provide quality services. Among the various aspects related to educational quality, administrative efficiency management has gained interest in recent times. This is due to the need to optimize resources and streamline the daily operations of an educational institution. This scoping review examines how efficiency is being measured in Higher Education Institutions (HEIs). Taking as a reference the proposed methodology by Arksey and O'Malley and the PRISMA Scr (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guide, we performed a search of the literature in the Scopus database from 2017 to 2022. As a result, different ways to measure administrative process efficiency were found, such as formulated models, methods, and indicators that show quantitative benefits. A significant finding was Lean or Six Sigma practices to improve administrative efficiency, in addition to the consideration of the interest group opinion through the application of measurement instruments to measure the impact on the user satisfaction level.